2019
DOI: 10.1371/journal.pone.0224616
|View full text |Cite
|
Sign up to set email alerts
|

The role of stigma in the acceptance and disclosure of HIV among recently diagnosed men who have sex with men in Australia: A qualitative study

Abstract: BackgroundOur primary study aimed to explore the experiences of men who have sex with men (MSM) recently diagnosed with HIV and their partner notification practices. Themes relating to acceptance, and disclosure of, their HIV status strongly emerged during analysis in our larger study and are reported separately here.MethodFifteen MSM participated in semi-structured interviews by phone or face to face about their experience of a recent HIV diagnosis. In this paper we report on how they received and accepted th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 32 publications
1
35
0
2
Order By: Relevance
“…This decline was due to the reason highlighted earlier. Index testing is shown to improve positivity rates and testing efficiency, 7,8 which in this study also improved our chances of identifying more positive individuals, even though index clients sometimes were reluctant to provide information about their sexual partners due to stigma and fear of rejection 24 as observed by low overall elicitation ratio of 1.7:1. The overall positivity rate from the index testing stream in this study was 21.4%, which implied that every 1 out of 5 partners tested was positive.…”
Section: Discussionmentioning
confidence: 70%
“…This decline was due to the reason highlighted earlier. Index testing is shown to improve positivity rates and testing efficiency, 7,8 which in this study also improved our chances of identifying more positive individuals, even though index clients sometimes were reluctant to provide information about their sexual partners due to stigma and fear of rejection 24 as observed by low overall elicitation ratio of 1.7:1. The overall positivity rate from the index testing stream in this study was 21.4%, which implied that every 1 out of 5 partners tested was positive.…”
Section: Discussionmentioning
confidence: 70%
“…MSM who have been rejected from their family are highly likely to have mental health issues, suicidal tendencies, depression, and highrisk sexual behavior (Katz-Wise et al, 2016;Ryan et al, 2010;Woodward & Pantalone, 2016;Bidaki et al, 2017). However, MSM who have strong social support seems to have fear of rejection into their family (Bilardi et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The main barrier for partner notification and serostatus disclosure was the fear of negative consequences associated with HIV-related stigma. A study in Australia similarly reported that, because of prevailing HIV stigma, most MSM were very selective about who they disclosed their status to, often only telling partners perceived at risk [ 35 ]. Nevertheless, since most participants in our study had experiences with informal partner notification despite stigma concerns, Mexican health care institutions could use this willingness to share an HIV diagnosis with partners and provide professional services that help avoid or mitigate stigma’s consequences.…”
Section: Discussionmentioning
confidence: 99%